IMPROVEMENT OF SYSTEMS OF TECHNICAL WATER SUPPLY WITH COOLING TOWERS FOR STEAM POWER PLANTS TECHNICAL AND ECONOMIC INDICATORS PERFECTION. Part 1 - Yu. A. Zenovich-Leshkevich-Olpinskiy; N. V. Shiroglazova; A. Yu. Zenovich-Leshkevich-Olpinskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In order to reduce the temperature of cooling water and increase the efficiency of use of power resources the main directions of modernization of systems of technical water supply with cooling towers at steam power plants are presented. The problems of operation of irrigation systems and water distribution systems of cooling towers are reviewed. The design of heat and mass transfer devices, their shortcomings and the impact on the cooling ability of the cooling tower are also under analysis. The use of droplet heat and mass transfer device based on the lattice polypropylene virtually eliminates the shortcomings of the film and droplet-film heat and mass transfer devices of the cooling tower, increasing lifetime, and improving the reliability and efficiency of the operation of the main equipment of thermal power plants. The design of the water distribution devices of cooling towers is also considered. It is noted that the most effective are water-spattering low-pressure nozzles made of polypropylene that provides uniform dispersion of water and are of a high reliability and durability.